2016
DOI: 10.1177/2325967116655742
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Among Professional Basketball Players

Abstract: Background:Vitamin D plays an important role in several systems of the human body. Various studies have linked vitamin D deficiency to stress and insufficiency fractures, muscle recovery and function, and athletic performance. The prevalence of vitamin D deficiency in the elite athletic population has not been extensively studied, and very few reports exist among professional athletes.Hypothesis:There is a high prevalence of vitamin D deficiency or insufficiency among players attending the National Basketball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
(64 reference statements)
1
43
0
Order By: Relevance
“…Previous results revealed a positive effect of vitamin D supplementation on global muscle strength, power and muscle fatigue risk factors [15,16,18,37]. The effectiveness of the vitamin D supplementation was confirmed in athletes, however, the optimal intake and serum 25(OH)D levels have yet to be identified in the athletic population [2,3].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous results revealed a positive effect of vitamin D supplementation on global muscle strength, power and muscle fatigue risk factors [15,16,18,37]. The effectiveness of the vitamin D supplementation was confirmed in athletes, however, the optimal intake and serum 25(OH)D levels have yet to be identified in the athletic population [2,3].…”
Section: Discussionmentioning
confidence: 98%
“…Endurance training has been associated with adaptive changes in skeletal muscle, such as an ability to use oxygen to generate energy for muscle work, a decrease in oxygen demand for the same level of external work performed [1], and a modification in markers of muscle damage and inflammation [2]. In a recent study, a prevalence of vitamin D deficiency in extreme endurance athletes, and an association between a delayed physical performance and a deficiency in vitamin D were observed during regular training [2][3][4]. These physiological responses in skeletal muscles were influenced by exercise-induced mechanisms and were probably affected by the nutritional athletic status and a limitation of sun exposure [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Holick 5 found no connection between latitude and serum vitamin D levels, 5 whereas Jelinek et al 16 The primary outcome of interest was the average levels of 25(OH)D in students between the campuses and their relationship to latitude. We acknowledge that literature has recognized deficient, insufficient, and sufficient ranges of vitamin D [10][11][12] ; however, for the purposes of this study's data analysis, levels were dichotomized to be either deficient or nondeficient, with deficient being recognized as less than 20 ng/mL. Participant demographics are presented in Table 1.…”
mentioning
confidence: 99%
“…Not surprisingly, the prevalence of poor vitamin D status in elite athletes is not exclusive to the NFL as nearly 80% of National Basketball Association (NBA) players at the annual combine had insufficient stores. 4 Although Dr. Fishman's study only focused on prevalence, it is not a stretch to believe that we would see similar predictive values of vitamin D levels associated with lower extremity injury in the elite basketball population. Although I do agree with the paper in question as well as current literature on the topic 1,4,5 in that vitamin D deficiency is prevalent and has deleterious effects in elite athletes, we cannot ignore the demographics of the study population.…”
Section: See Related Article On Page 1280mentioning
confidence: 95%
“…4 Although Dr. Fishman's study only focused on prevalence, it is not a stretch to believe that we would see similar predictive values of vitamin D levels associated with lower extremity injury in the elite basketball population. Although I do agree with the paper in question as well as current literature on the topic 1,4,5 in that vitamin D deficiency is prevalent and has deleterious effects in elite athletes, we cannot ignore the demographics of the study population. In particular, the majority of these athletes are black (NFL 69.7%; NBA 74.4%) and thus have a significant predisposition to vitamin D deficiency.…”
Section: See Related Article On Page 1280mentioning
confidence: 95%